METHOD FOR IDENTIFYING HAZARDOUS ROAD LOCATIONS AT THE INTERSECTION OF TRAMLINES AND ROAD TRAFFIC - Renata ŻOCHOWSKA; Piotr SOCZÓWKA (Scientific Journal of Silesian University of Technology. Series Transport)
Passenger transport safety is an important issue. This paper presents a method for the identification of locations at the intersection of tramlines and road traffic, which are characterized by a high level of risk. Furthermore, different aspects of risk have been determined in order to analyse the problem in a complex way. For each aspect of risk, a measure was developed to estimate the level of risk. The application of the proposed method has been presented on the basis of an analysis of documentation of traffic incidents on the tram network. Accordingly, hazardous road locations have been identified.